Not in an Ivory Tower: Zev Garber and Biblical Studies - Greenspoon, Leonard J. 1945- (2010)
Passion and commitment are two of the defining characteristics of Zev Garber’s scholarship and of his approach to life. Students can immediately identify and identify with these features; moreover, many of Garber’s colleagues have followed his lead in stepping down from the pristine environment of the ivory tower into the messy realities of life as it is being, and has been, led throughout human history.